2017
DOI: 10.12783/dtetr/amma2017/13353
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Detection with the Global GPS Information System

Abstract: The Intergovernmental Panel on Climate Change (IPCC) has predicted a persistent and wide-spread warming of temperatures close to the surface over the entire globe in the 21 st century, due to the continuously increases in the concentrations of anthropogenic greenhouse gases in the atmosphere. How realistic are the predictions made by the IPCC models, especially over the polar region where the highest increases in temperatures were predicted? Due to the lack of accurate temperature measurements over polar regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Anthes et al, (2001) [5] explains that, especially in remote oceanic regions, COSMIC water vapor profiles would enable scientists to monitor the response of the global atmosphere to regional events such as atmospheric rivers. Wang (2017) [6] analyzed the COSMIC data from 2007 to 2016, which demonstrated that a significant warming has occurred during that time period, and most pronounced warming areas had occurred over the polar region. The pronounced warming over the polar region is exacerbating sea ice loss and melting glaciers.…”
Section: Introductionmentioning
confidence: 99%
“…Anthes et al, (2001) [5] explains that, especially in remote oceanic regions, COSMIC water vapor profiles would enable scientists to monitor the response of the global atmosphere to regional events such as atmospheric rivers. Wang (2017) [6] analyzed the COSMIC data from 2007 to 2016, which demonstrated that a significant warming has occurred during that time period, and most pronounced warming areas had occurred over the polar region. The pronounced warming over the polar region is exacerbating sea ice loss and melting glaciers.…”
Section: Introductionmentioning
confidence: 99%